Cross sections for vibrational excitation and dissociative recombination of the CF3+ ion in collisions with low-energy electrons. (1st April 2022) - Jiang, Xianwu; Liu, Hainan; Zhang, Ya; Jiang, Wei; Ayouz, Mehdi; Kokoouline, Viatcheslav
Abstract: Cross sections for the vibrational excitation and dissociative recombination (DR) of the C F 3 + ion in collisions with electrons at low scattering energies are computed using a previously-developed approach combining the normal mode approximation for the vibrational states of the target ion and the UK R -matrix code for the evaluation of the scattering matrices at fixed geometries. The obtained cross section for the DR shows excellent agreement with the experimental data from the ASTRID storage ring. Thermally-averaged rate coefficients are obtained from the cross sections for temperatures 10–3000 K.